Fostering A Culture Of Collaboration During International Pre-Service Teacher Field Placements: The Power Of Mentor Teachers - Boury, Tiffany T. (European Scientific Journal, ESJ, 2016)
This paper reports the results of an action-research case study that investigated the data submitted over three semesters by particpating preservice teachers in an international field experience. The investigation highlights what the the author has determined to be critical components in the implementation of Social Cohesion and effective mentoring by cooperating Austrian teachers .